Accounting Analysis of Raudhatul Muhajirin Islamic Boarding School Jambi Based on Boarding Accounting Guidelines - Natalia Fitria Revini Pranata; Nela Safelia; Gandy Wahyu Maulana Zulma; Wiwik Tiswiyanti; Fredy Olimsar (International Journal of Integrative Sciences, 2023)
The purpose of this research is to learn about financial records, the application of Islamic boarding school accounting guidelines in preparing financial reports, and the type of financial reporting that follows Islamic boarding school accounting guidelines. This is a descriptive study that employs qualitative methods. Primary and secondary data were used to collect data for this study. Primary data is the result of interviews, questionnaires, and observations based on a prepared list of questions. Meanwhile, secondary data comes from the Raudhatul Muhajirin Islamic Boarding School's financial reports in the form of income and expenditure reports. The findings revealed that the accounting treatment used in the preparation of financial reports at the Raudhatul Muhajirin Islamic Boarding School did not meet Standar Akuntansi Keuangan untuk Entitas Tanpa Akuntabilitas Publik (SAK ETAP), and the financial statements prepared did not meet the Islamic boarding school's accounting guidelines. It is hoped that the research findings can provide knowledge and input, especially for Islamic boarding school administrators, regarding the importance of Islamic boarding school accounting guidelines. Which guidelines based on SAK ETAP aim to provide uniformity and become one of the efforts to improve governance in Islamic boarding schools